Varicella-Zoster Virus Vasculitis: A Case Report of Enteric Reactivation with Vasculopathy Leading to Arterial Dissection, Stroke, and Subarachnoid Hemorrhage - Donohoe, Charles; Gui, Zhenhua; Nia, Nooshin Kiani (Archives of Clinical and Medical Case Reports, 2021)
Varicella-Zoster virus (VZV) reactivation is known to cause vascular remodeling and creating a hypercoagulable state, which can result in vasculopathy and subsequent thrombotic complications. Frequently, these complications involve intracranial and extracranial arteries leading to ischemic stroke, cerebral aneurysm formation, subarachnoid hemorrhage, cerebral vasculitis, and giant cell arteritis. Symptoms involving veins, such as cerebral sinus thrombosis, deep venous thrombosis, and pulmonary embolism, are rare. VZV reactivation is classically identified in neuronal ganglia that are derived from neural crest cells, primarily the dorsal root ganglia with the typical zoster dermatomal rash. In addition to the dorsal root ganglia, the enteric nervous system and adrenal glands are also of neural crest origin. However, VZV reactivation in these regions is rarely recognized due to a lack of cutaneous innervation. Enteric VZV reactivation can present with vague gastrointestinal symptoms instead of the typical zoster skin rash, which may be overlooked and delay the diagnosis. We report a rare case of VZV reactivation in the enteric nervous system and adrenal gland leading to vasculitis and subsequent Subarachnoid Hemorrhage (SAH), multifocal ischemic stroke, right Internal Carotid Artery (ICA) dissection, Deep Venous Thrombosis (DVT), and Pulmonary Embolism (PE).